THE HISTORY OF THE USA, PRE-COLONIAL AMERICAN LIFE, EUROPEAN DISCOVERY - Teshaboyeva Nafisa Zubaydulla qizi; Mamadaminova Nigina Maxkam qizi (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This comprehensive article traces the multifaceted journey that led to the establishment of the United States of America. Divided into two key sections, it meticulously examines the pre-colonial American landscape and the pivotal era of European discovery and exploration, providing a nuanced understanding of the nation's origins. The article culminates by acknowledging the far-reaching implications of European colonization, setting the stage for the formation of the United States while recognizing the profound challenges and conflicts that arose from this period.